Książki i czasopisma wydawane we Lwowie w XIX i na początku XX wieku – ze zbiorów Biblioteki Głównej Akademii Pedagogicznej (wystawa) - Tłuczek, Ewa; Zając, Renata (AUPC Studia ad Bibliothecarum Scientiam Pertinentia, 2005)
[Books and Magazines Published in Lvov in 19th and Beginning of 20th Centuries - from the Collection of the Main Library of the Pedagogical University (Exhibition)] The article presents the most interesting specimens of books and journals in the collec-tion of the Main Library of the Pedagogical University of Cracow, which were published in Lvov in the 19th and beginning of 20th centuries. What is also commented on is the history of Lvov publishing houses which were exhibited. Numerous pedagogical and psychological books discussed in the article also deserve attention.